Workplace Software and Skills - Bolling, Tammie; Mitchell, Angela; Scott, Tanya; Wheeler, Nyrobi; Lepore, Bridget; Walton, Janine; Burgoyne, Timothy; Arguello, Rick; Falduto, Valeree (Open textbook library., 2023)
Workplace Software and Skills is designed to flexibly support a range of courses covering computer literacy, Microsoft Office, and Google Suite applications. The textbook covers both hard and soft skills that are applicable to a broad range of academic majors and careers. Chapters combine studio learning and guided practice with scaffolded activities designed to reinforce a student’s ability to perform higher-order tasks independently. Workplace Software and Skills leverages complementary product features in spreadsheet, word processing, presentation, and similar applications. Modules are designed for maximum flexibility by including both Microsoft Office Suite and Google Suite applications, in order to best reflect the skills needed for today’s workforce. Authentic activities and real-world contexts develop a cumulative and thorough understanding, which reinforces the importance of cross-platform proficiency. Highly visible features also note Apple/Mac functions as needed.